2008
DOI: 10.4322/rbeb.2012.050
|View full text |Cite
|
Sign up to set email alerts
|

MINERSUS Ambiente computacional para extração de informações para a gestão da saúde pública por meio da mineração dos dados do SUS

Abstract: Resumo O objetivo deste trabalho é apresentar a definição, implementação e validação de um ambiente computacional, denominado MINERSUS, para a produção de informação analítica por meio da mineração das bases de dados dos sistemas de informações do Sistema Único de Saúde (SUS). A partir de uma revisão bibliográfica e de um projeto desenvolvido na Secretaria Estadual de Saúde (SES-SP) (Santos et al., 2004 e 2006), levantou-se uma lista de desafios para implantar uma ferramenta analítica na área da saúde. Mediant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
2
0
4
Order By: Relevance
“…In Brazil, other data warehouses have been developed based on the SUS data files (Pires, 2011;Santos and Gutierrez, 2008). Santos and Gutierrez (2008) developed a data warehouse from SIA, SIH, SIM, and other systems for the State of São Paulo without identifying the patients and developed a bespoken tool, called MINERSUS, to support data mining as well. Pires (2011) advanced one step further and integrated the systems in the previous work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, other data warehouses have been developed based on the SUS data files (Pires, 2011;Santos and Gutierrez, 2008). Santos and Gutierrez (2008) developed a data warehouse from SIA, SIH, SIM, and other systems for the State of São Paulo without identifying the patients and developed a bespoken tool, called MINERSUS, to support data mining as well. Pires (2011) advanced one step further and integrated the systems in the previous work.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it is necessary to generate performance indicators (effectiveness, cost, adverse events among others) of the technologies in use and not only production indicators. This is possible due to the availability and access to SUS health information systems (mortality information system -SIM in Portuguese, hospital information system -SIH-SUS in Portuguese, outpatient information system -SIA-SUS in Portuguese, among others) (DATASUS, 2013) and the possibility of integrating the data records of these systems (Freire et al, 2012;Gomes and Almeida, 2004;Pires, 2011;Queiroz et al, 2009;Santos and Gutierrez, 2008). In cancer care, studies have demonstrated the possibility of linking records for generating indicators for the estimation of the required infrastructure, the follow up of clinical guidelines and the effectiveness of a screening program (Bastos, 2011;Costa, 2005;Gomes and Almeida, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, existem experiências de desenvolvimento de sistemas que geram informações úteis para a gestão a partir das bases de produção dos sistemas implantados pelo DATASUS, destacando-se os trabalhos de Mussi et al 15 e o de Santos et al 16 . O SISONCO difere destes por permitir a identificação dos casos de câncer e a recuperação de seus históricos de tratamento no APACSIA/SUS, propiciando a análise longitudinal dos casos tratados.…”
Section: Discussionunclassified
“…Os dados existentes nestas bases de dados permitem estimar custos de tratamento, prever epidemias e adotar procedimentos terapêuticos e preventivos para melhorar a condição de vida da população. Entretanto, apesar da abrangência dessas bases de dados, que reúnem informações nos diversos níveis de atenção, ainda não é possível analisar tais informações de maneira conjunta e em uma visão única integrada e interoperável [1,2].Além das questões de falta de interoperabilidade entre bases, há um grande desafio em melhorar o fluxo atual de coleta de dados na atenção básica, pois a qualidade da informação é influenciada pelos instrumentos de coleta, que em sua grande maioria utilizam o registro e anotações em papel [3].…”
Section: Introdução Atasus é O Departamento De Informática Do Miniunclassified